Ukrainian urban vernacular garden: reconsideration in the conditions of full-scale war - Butsykina, Yevheniia (Ukrainian Cultural Studies, 2022)
The paper contents a cultural analysis of the vernacular garden as a phenomenon of popular urban culture, as well as the transformation (politicization) of its role and perception in the conditions of martial law. The garden analysed at different levels: individual (gardening is an individual practice of a citizen), local (features of the local community, its values, lifestyle, common practices, problems, etc.), as well as at the level of tradition and culture. Structural analysis of the garden as a multifunctional space allows us to identify individual functions of this phenomenon. After all, by creating a home-made garden, a city dweller satisfies his needs in this way, and not only needs for products, but most often those of a social and cultural nature.The main characteristics of the vernacular garden were revealed: structure, non-utilitarianism, procedure. The main functions of the garden are socio-political, humanitarian, food, aesthetic, educational, unifying, educational, and entertaining. Ukrainian vernacular gardening is compared with other formats of urban gardening, which have a combination of different goals and corresponding functions: "community garden", Victory gardens and guerrilla gardening. In contrast to guerrilla gardening, vernacular gardening does not initially have political intentions – to fight against the state of neglected urban areas, to draw the attention of local citizens to the problems of the district. It was determined that the individual vernacular garden acquires a new meaning in the conditions of martial law: it becomes one of grassroots initiatives, practices of resistance, stability and steadfastness. Vernacular horticulture as an individual grassroots practice is a bright and promising mediator of important social and political processes that Ukrainian society is going through in times of full-scale war.The political aspects of urban vernacular gardening also touch on feminist issues. Usually, women are gardeners, and this fact is worth a separate study, because it is women who implement these practices and, accordingly, changes in the urban landscape, according to their botanical and aesthetic preferences, favourite plants and cultures.
Keywords: vernacular garden; war; public garden; guerilla gardening; everyday urban culture; Victory Gardens